Fifteen years of biological control of Diatraea saccharalis using parasitoids - Botelho, Paulo Sérgio Machado (Pesquisa Agropecuaria Brasileira, 1992)
This paper reports the fifteen years of research activities at IAA/PLANALSUCAR - COSUL (Southern Coordination Service) on biological control of sugar cane borer, Diatraea saccharalis, in the sugar cane belt covering the states of São Paulo, Paraná, Minas Gerais, Mato Grosso do Sul and Mato Grosso. Emphasis is given to the results obtained with the main larval parasitoids, the native flies Metagonistylum minense and Paratheresia claripalpis, and the introduced wasp, Apantelis flavipes = Cotesia flavipes. A biological control program involving large scale mass production of A. flavipes was established. It is now one of the broadest and most effective program of the kind in the world.
Keywords: Metagonistylum minense; Paratheresia claripalpis; Apanteles flavipes